2020
DOI: 10.1021/acs.jcim.0c01079
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminus of the Third PDZ Domain of PSD-95 Orchestrates Allosteric Communication for Selective Ligand Binding

Abstract: PDZ domains constitute common models to study single-domain allostery without significant structural changes. The third PDZ domain of PSD-95 (PDZ3) is known to have selective structural features that confer unique modulatory roles to this unit. In this model system, two residues, H372 directly connected to the binding site and G330 holding an off-binding-site position, were designated to assess the effect of mutations on binding selectivity. It has been observed that the H372A and G330T-H372A mutations change … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…This is a result of the close-knit character of DM complexes, having more hydrogen bonds at the binding pocket and low overall solvent accessibility, as quantified in detail in our previous study. 20 Although the averages are similar, the number of broken edges fluctuate over the course of the trajectories (Figure S3). These changes indicate that the configurations for information flow are modified throughout the MD trajectories.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…This is a result of the close-knit character of DM complexes, having more hydrogen bonds at the binding pocket and low overall solvent accessibility, as quantified in detail in our previous study. 20 Although the averages are similar, the number of broken edges fluctuate over the course of the trajectories (Figure S3). These changes indicate that the configurations for information flow are modified throughout the MD trajectories.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…In a recent study, we have investigated the relative binding energies of PDZ3 complexes using classical MD trajectory analyses and free energy perturbation calculations, and we have shown that the generated MD trajectories sample adequate conformational range to reproduce the experimentally measured binding affinities. 17,20 In particular, we have found that the interplay between protein−ligand hydrogen bonding, solvation free energy of the complex, and the dynamics of the highly charged N-terminus are the three main factors that determine the binding fate of the ligand. 20 In fact, it has been possible to compute the free energy difference values corroborating experimentally measured binding constants using various advanced simulation techniques and to break down the contribution of each of these factors by a simplified model.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations